Multichannel photoionization of cold strontium atoms - Ruan, Shushu; Han, Yongyan; Shen, Zhenjie; Yu, Xinglong; Fang, Yong-Kang; Wang, Xincheng; Chen, Ahai; Liu, Jie; Wu, Zhixian; Ueda, Kiyoshi; Weidemüller, Matthias; Zhu, Bing; et al. (Physical review, 2024)
The multichannel single photoionization of cold strontium atoms is investigated experimentally and theoretically with 800-nm femtosecond laser pulses of 35-fs duration at laser intensities of 3-6 TW/cm2. The photoelectron energy spectra exhibit rich multipeak structures, which are identified as the multichannel ionization of the ground state 5⁢𝑠2⁢1⁢𝑆0 and excited states 5⁢𝑠⁢5⁢𝑝⁢1⁢𝑃1, 5⁢𝑠⁢5⁢𝑝⁢3⁢𝑃2, and 5⁢𝑠⁢4⁢𝑑⁢1⁢𝐷2. The photoelectron momentum distributions reveal distinct structures, and the corresponding photoelectron angular distributions provide valuable insights into the multiphoton ionization dynamics. As the laser intensity increases, the locations of the photoelectron energy peaks originating from the ionization of the excited states 5⁢𝑠⁢5⁢𝑝⁢3⁢𝑃2 and 5⁢𝑠⁢5⁢𝑝⁢1⁢𝐷2 remain unshifted, indicating the existence of Freeman resonance. The profiles from numerical solutions of the time-dependent Schrödinger equation (TDSE) are generally in agreement with the experimental results. However, some discrepancies, i.e., the ratio of partial waves contributing to the final states and tiny structures caused by resonance, may arise from the incomplete modeling of the valence-electron correlation effect in the present TDSE simulations based on the single-active-electron approximation.
Online veröffentlicht: 23. September 2024
Gesehen am 16.04.2025